Acupuncture for perimenopausal depressive disorder: A systematic review and meta-analysis protocol - Feng, Jialei (Medicine (Baltimore), 2019)
BACKGROUND: Perimenopausal depressive disorder (PDD) is a disease that plagues many perimenopausal women. There is an urgent need for a safe way to treat the disease. With few side effects, acupuncture treatment for PDD has been gradually accepted. However, at present, the evidence is insufficient and relevant studies are not in-depth enough. The purpose of this study is to explore the efficacy and safety of acupuncture for PDD. METHODS: All randomized controlled trials articles on acupuncture treatment of PDD will be searched in databases such as MEDLINE, EBASE, Cochrane Library, Springer, World Health Organization International Clinical Trials Registry Platform, China National Knowledge Infrastructure, Wan Fang, Chinese Biomedical Literature Database, Chinese Scientific Journal Database and so on. Non-RCT articles will be screened and key information will be extracted. The primary outcome is the Hamilton depression scale. Second outcomes are the Hamilton anxiety scale, Quality of life scale, changes of symptoms in traditional Chinese medicine and hormone levels. RESULTS: This systematic review will provide the highest level of evidence and provide an evaluation of the efficacy and safety of acupuncture for PDD. CONCLUSION: This study provides evidence for evaluating the efficacy and safety of acupuncture in the treatment of PDD. PROSPERO REGISTRATION NUMBER: CRD42018115811.